Clinical Findings and Diagnosis of Rabies Using Direct Fluorescent Antibodies Test (FAT) in Domestic Animals: DIAGNOSIS OF RABIES BY FLUORESCENT ANTIBODIES TEST - Kachhawaha, Subhash; R.K. Tanwar (Annals of Arid Zone, 2024)
Rabies is an important zoonotic disease of all warm-blooded animals. The present study was carried out in Jodhpur city of Rajasthan, India. In cattle and buffaloes, important clinical signs of rabies were bellowing, anorexia, high rise of temperature and hypersalivation whereas, in dogs changes in behaviour, aggressiveness and anorexia were the most common clinical signs. Biting and paralysis were the main signs in camel. In goat, head pressing and continuous bleating were observed the main symptoms. The diagnosis was done through brain sample collected from suspected cases of rabies after death. In present investigation, fluorescent antibody technique (FAT) was used in brain tissues of 82 rabies-suspected animals for diagnosis. Out of 82 brain tissue samples, 52 dogs, 8 buffaloes, 15 cows, 4 goats and 3 camels were examined for FAT test. Out of 82 rabies-suspected cases, 49 (59.75%) cases were found positive by FAT. On the basis of findings of our study it is proposed that FAT can be used as rapid diagnostic test for diagnosis of rabies in animals.